Idealisme dalam Evaluasi Kinerja Sekolah di SDN Cibalandongan - Muchtar, Hendi S.; Handayani, Sri; Jamaludin, Ayi; Nurlatifah, Fitri; Santosa, Santosa (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2024)
Abstract: This research aims to analyze how school performance is evaluated using the idealism theory approach at SDN Cibalandongan. Apart from that, this research also aims to determine the factors that hinder the implementation of school performance evaluations. This research uses a qualitative approach with a case study method. The data collection techniques used were observation, interviews and documentation. Data analysis was carried out using qualitative data analysis techniques. The research results show that in general teacher performance has shown good criteria, it's just that with changes to the curriculum, teachers need to be guided and accompanied. Performance assessment activities are carried out every semester as part of the learning process. At the beginning of the year, formative teacher performance assessments are used as a basis for determining self-evaluation and continuous professional development (PKB). Furthermore, in the following semester at the end of the year a summative teacher performance assessment is carried out. One way in which school performance is achieved is determined by the performance of teachers in carrying out their roles, duties and responsibilities as regulated in Law no. 14 of 2005 concerning Teachers and Lecturers, especially article 20 points a and b. Furthermore, teacher performance evaluation can be used as an effort to guarantee school quality, which is carried out by developing a valid and reliable instrument related to aspects of (1) personal development, (2) learning, (3) increasing professional abilities, and ( 4) social interaction with stakeholders. However, the tools and results obtained will not accelerate and improve school performance, if they are not followed up with capacity building programs for teachers.Key words: Idealism, Evaluation Of School PerformanceAbstrak: Penelitian ini bertujuan untuk menganalisis bagaimana evaluasi kinerja sekolah dengan menggunakan pendekatan teori idealisme di SDN Cibalandongan. Selain itu, penelitian ini juga untuk mengetahui faktor – faktor yang menghambat pelaksanaan evaluasi kinerja sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Analisis data dilakukan dengan menggunakan teknik analisis data kualitatif. Hasil penelitian menunjukkan bahwa secara umum kinerja guru sudah menunjukkan kriteria baik, hanya saja dengan perubahan kurikulum, guru perlu untuk dibimbing dan didampingi. Kegiatan penilaian kinerja dilakukan setiap semester sebagai bagian dari proses pembelajaran. Pada awal tahun penilaian kinerja guru formatif yang digunakan sebagai dasar   untuk   menentukan   evaluasi   diri   dan pengembangan keprofesian berkelanjutan (PKB). Selanjutnya pada semester berikutnya di akhir tahun dilakukan penilaian kinerja guru sumatif. Pencapaian kinerja sekolah salah satunya ditentukan oleh kinerja guru dalam melakukan peran, tugas, dan tanggungjawabnya sebagaimana diatur dalam Undang-undang No. 14 tahun 2005 tentang Guru dan Dosen khususnya pasal 20 poin a dan b. lebih jauh dari itu, evaluasi kinerja guru dapat dijadikan sebagau upaya untuk penjaminan mutu sekolah, yang dilakukan dengan mengembangkan suatu instrumen yang valid dan reliable terkait dengan aspek (1) pengembangan pribadi, (2) pemelajaran, (3) peningkatan kemampuan profesional, dan (4) interaksi sosial dengan stakeholder. Namun alat dan hasil yang didapat tidak akan menambah percepatan dan perbaikan kinerja sekolah, manakala tidak ditindaklanjuti dengan program capacity building bagi guru.Kata Kunci : Idealisme, Evaluasi Kinerja Sekolah